Budget-type techno-economic model for onshore CO2 pipeline transportation in China. (August 2016) - Wei, Ning; Li, Xiaochun; Wang, Qian; Gao, Shuai
Highlights: A budget type techno-economic model of onshore CO2 pipeline was developed. The model based on existing technical characteristics, guidelines, and budgetary parameters of CO2 pipelines. This model can provide more detailed estimates for specific CO2 pipeline projects. Cost ranges across different regions in China are evaluated. Abstract: CO2 pipeline transportation is a cost-effective technology for the transportation of large volumes of CO2 . Numerous published techno-economic models of CO2 pipelines primarily use pipeline length and another quantity, such as pipe diameter, flow rate, and flow velocity, to predict the cost of a pipeline project. The precision of such economic models is limited by the technical characteristics of CO2 pipelines and the scarcity of statistical data from natural gas pipelines, especially in China. Therefore, building budgetary techno-economic models to assess cost with less uncertainty under increased flexible conditions is essential. A budget-type techno-economic model for an onshore CO2 pipeline was established based on existing technical guidelines, budgetary parameters, and technical characteristics of CO2 pipelines. This model can be used to provide more detailed estimates for specific CO2 pipeline projects. The cost ranges of CO2 pipelines across different regions in China were studied using deterministic and stochastic analyses. The mean values and variation ranges of levelized costs in Central, East, Northeast, North, Northwest, and South China were obtained and analyzed. This study provides highly detailed cost results for onshore CO2 pipeline projects in China.